Analysis of Project Delay Impacts on Time and Cost In Elevator Work For A 10-Story Office Building Construction Project - Oktafiansyah, Turmudi; Patriadi, Andi; Sajiyo, Sajiyo (Devotion : Journal of Research and Community Service, 2025)
This study aims to analyze the impact of elevator installation delays on the schedule and budget of a 10-story office building construction project in Gresik. By comparing two scenarios—on-time elevator work versus delayed elevator work—this research uses a comparative analysis approach based on project documentation, interviews with stakeholders, and cost and time data. The findings reveal that delays in elevator work significantly affected the overall project timeline, causing a shift in the schedule and necessitating changes in structural methods, particularly the use of steel instead of concrete for the separator beams. This change expedited construction but increased costs substantially. The study also highlights the cascading effects of these delays, which led to further adjustments in the building's structure and increased labor and material costs. The research emphasizes the importance of early-stage planning, coordination, and the adoption of advanced project management techniques, such as Building Information Modeling (BIM), to minimize risks and ensure timely project completion. In conclusion, the study provides valuable insights into how elevator delays can disrupt construction projects and recommends strategies to mitigate such risks in future developments.